An Evaluation of Epidural Bupivacaine with and without Meperidine in Labor. Issue 1 (January 1992) - Brownridge, P.; Plummer, J.; Mitchell, Jill; Marshall, P.
Abstract : Background: One aim of epidural analgesia during childbirth is to provide satisfactory pain relief with minimal side effects. We hypothesized that a combination of opioid and local anesthetic would better achieve this aim than either drug alone. This study compared the efficacy and side effects of epidural meperidine and bupivacaine combined to those of meperidine and bupivacaine alone. Methods: One hundred consenting nulliparas requesting epidural analgesia in labor were randomly assigned to receive, in a double-blind fashion, one of five treatments. These were 25 mg meperidine, 12.5 mg bupivacaine, 25 mg meperidine plus 12.5 mg bupivacaine, 25 mg bupivacaine, and 37.5 mg bupivacaine. Efficacy of analgesia and side effects were assessed before and after each dose. Leg strength was measured with a force meter and blood flow to each foot with a blood perfusion monitor. The neurobehavioral state of the newborn was assessed by a pediatrician who was blind to treatment using a neurologic and adaptive capacity scoring system. Results: Thirty-seven women did not achieve satisfactory analgesia after the first dose of test medication; these predominantly were those who received 25 mg meperidine ( n = 12) or 12.5 mg bupivacaine ( n = 11). Nausea decreased after the initial dose with all treatments ( p < 0.01), whereas shivering increased in patients receiving bupivacaine ( p < 0.01). There was a reduction in leg strength and an increase in blood flow associated with the two higher bupivacaine treatments ( p < 0.01), and with both parameters the dependent limb was most affected. Overall patient satisfaction was greatest in the group receiving meperidine plus bupivacaine. Neonatal neurologic and adaptive capacity scores did not differ significantly among the treatment groups. Conclusion: The low-dose combination of meperidine and bupivacaine used in this trial proved a satisfactory preparation for epidural administration during the early stages of labor.